Age-related viral load and severity of systemic pathological lesions in acute naturally occurring African swine fever virus genotype II infections. (December 2021) - Oh, Taehwan; Do, Duy Tien; Lai, Danh Cong; Nguyen, Thanh Che; Vo, Hung Van; Chae, Chanhee
Abstract: African swine fever (ASF) causes a contagious hemorrhagic disease in all ages of pigs without sex predilections. The objective of this study was to determine the age-related viral loads and severity of systemic pathological lesions among three different swine group ages (weaned pigs, fattening pigs, and sows) during a recent outbreak of acute ASF in Vietnam. Age-related viral loads were determined in 5 major organs (lung, liver, spleen, kidney, and lymph node) by immunohistochemistry as well as in the blood by real-time polymerase chain reaction (PCR). Age-related systemic pathological lesions were analyzed in the listed organs among three age groups. Weaned pigs had significantly ( p < 0.05) higher levels of viral loads in their lung, liver, lymph nodes and blood than in those of fattening pigs and sows. Fattening pigs had significantly ( p < 0.05) higher scores of macroscopic lung and lymphoid lesions, and microscopic liver lesions compared with those of weaned pigs and sows. The results of this study demonstrated that viral loads were age-related in acute naturally occurring ASF but the severity of pathological lesions was not correlated with the level of viral loads in the five major organs. Highlights: A comparative pathological investigation was conducted with three different age groups of pigs in acute naturally occurring ASF. Viral replication was age-related but the severity of lesions was not consistent with viral load in five major organs. The field evidence in this study suggested that age factor may affect ASF pathogenesis.